Про формування сталого ланцюга постачань - Россолов, Олександр; Лобашов, Олексій (Посвіт, 2019)
Urbanization of the population is one of the main trends of the 21st century. The increase of the urban population has already led to a set of problems today: an increase of the environmental pollution in cities, an increase of the noise level due to a rise of the automobilization level, exacerbation of the problems of garbage disposal. In such conditions, the concept of sustainable cities should be extended to the concept of sustainable urban-suburban areas, for which the formation of eco-friendly transport, retail, and entertainment infrastructure becomes relevant.
About sustainable supply chain formation
Keywords: 656.073